PENERAPAN STRATEGI PAKET OPEN TRIP DAN KUALITAS PELAYANAN JASA DALAM MEMPENGARUHI KEPUTUSAN PEMBELIAN KONSUMEN PT. ROMI TOUR AND TRAVEL SEBAGAI AGEN BIRO PERJALANAN WISATA - Amri, Adi Ihsan Syukri; Hamdiah, Hamdiah; Utami, Febby Nanda; Beatrice, Aulia; Auliah, Syahrani Rabi (Manajerial dan Bisnis Tanjungpinang, 2025)
This study aims to analyze whether the variables of open trip strategy and service quality, both partially and simultaneously, have an influence on the consumer purchase decision variable at PT Romi Tour and Travel as a travel agency. The object of this research is consumers who have used the services of PT Romi Tour and Travel as a travel agency, with a total sample of 96 respondents determined using the Cochran formula. The data were collected through questionnaires randomly distributed to consumers who used the services of PT Romi Tour and Travel as a travel agency via Google Forms. The data analysis methods used in this study include multiple regression analysis, coefficient of determination analysis, classical assumption tests, F-test, and t-test. The results of the study indicate that both simultaneously and partially, the variables of open trip package strategy and service quality have an influence on the consumer purchase decision variable.